Freddie's War - Rollason, Jane (United Kingdom Cambidge University Press, 2010)
It is 1936 and Europe is on the road to war. Freddie is a working-class English boy who is desperate for more excitement in his life. When he reads about foreign volunteers heading to the war in Spain, he knows what he must do
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents
Keywords: Fiction; Reading books; English language; Language Learning; Historical story